The vagus nerve mediates the physiological but not pharmacological effects of PYY3-36 on food intake - Aldara Martin Alonso; Simon C. Cork; Phyllis Phuah; Benjamin Hansen; Mariana Norton; Sijing Cheng; Xiang Xu; Kinga Suba; Yue Ma; Georgina KC. Dowsett; John A. Tadross; Brian YH. Lam; et al. (Elsevier, 2024)
Peptide YY (PYY3-36) is a post-prandially released gut hormone with potent appetite-reducing activity, the mechanism of action of which is not fully understood. Unravelling how this system physiologically regulates food intake may help unlock its therapeutic potential, whilst minimising unwanted effects. Here we demonstrate that germline and post-natal targeted knockdown of the PYY3-36 preferring receptor (neuropeptide Y (NPY) Y2 receptor (Y2R)) in the afferent vagus nerve is required for the appetite inhibitory effects of physiologically-released PYY3-36, but not peripherally administered pharmacological doses. Post-natal knockdown of the Y2R results in a transient body weight phenotype that is not evident in the germline model. Loss of vagal Y2R signalling also results in altered meal patterning associated with accelerated gastric emptying. These results are important for the design of PYY-based anti-obesity agents.